Computer organization and design the hardware/software interface - Hennessy John L; Patterson David A (San Francisco Morgan Kaufmann, 1998)
This book provides a framework for thinking about computer organization and design. The text focuses on the boundary between hardware and software & explores the levels of hardware in the vicinity of the boundary. It builds on introductory programming sk
Keywords: Computer organization; Computers-design and construction